ABC Smart Coffee Maker: A Young Techno Start-Up. Issue 1 (March 2022) - Wongtada, Nittaya
A team of three young entrepreneurs formed the Auroma Brewing Company (ABC) in November 2014 right after their graduation from the University of British Columbia, Canada. Their first product was a smart coffee maker which could brew coffee with high precision, allowing users to experiment with variations in the brew. After successfully raising funds online in January 2016, they moved to Shenzhen, China, to manufacture the device. The initially promised shipment date was August 2017, but—as of October 2017—the backer and pre-order buyers were still waiting for their smart coffee maker. The team had faced several obstacles in outsourcing parts to various manufacturers, which caused several delays in shipping the device to the backers who had supported their project through the crowdfunding platforms. After the first delay, about one-tenth of the backers withdrew their supports . After successive delays, the remaining backers became more agitated and questioned the team's ability to deliver the smart coffee device successfully. Detecting the market potential of ABC's device, a large company had proposed to acquire ABC's technology. The team wondered whether they should accept the offer or if they should explore other opportunities.